Rancang Bangun Sistem Point Of Sales Berbasis Website Dengan Metode Waterfall (Studi Kasus: Yoboya Pasar Kemis) - Nuraeni; Salman Farizy (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
Yoboya Pasar kemis, is a cafe that sells various kinds of food and drinks. So far, the recording of transactions is still using the manual written in the book. So that in this process errors often occur in recording sales due to untidy filing and the difficulty of finding existing transaction data. The problem to be solved is how to design a website-based Point Of Sales (POS) application at the Yoboya cafe using the Waterfall system development method, namely with the stages: analysis, design, implementation, testing, maintenance. The result of this research is a website that can display sales graphs and sales profits making it easier to monitor sales developments at Yoboya itself, and the design of this websitebased application is made with an easy to understand interface so that users will find it easier to use